The Personalistic System of Healthcare in Indonesia: A Case Study - Deddy Mulyana; Dadang Rahmat Hidayat; Susanne Dida; Tine Silvana; Siti Karlinah; Jenny Ratna Suminar; Asep Suryana (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
The healthcare reality is composed of biomedical, naturalistic, and personalistic systems. Although the three healthcare systems go separately, to some extent they are overlapped. This study aims to explore alternative healing practices in Indonesia based on the personalistic system. The method used is a case study. Data was collected in several big cities (Bandung, Jakarta, Yogyakarta, Surabaya, Palembang, Batam and Makassar) in Indonesia through Focus Group Discussion (FGD) with stakeholders of healthcare programs on media, interviews with physicians, alternative therapists and patients, observation of alternative therapies, and media content analysis. The results indicate that the healthcare practices based on the personalistic system is widespread throughout Indonesia, including religious treatment (often called ruqyah) involving religious chants and prayers. With some using herbal medicine, a lot of alternative therapies based on the personalistic system have been promoted through word of mouth (interpersonal communication) by common people as patients as well as through the electronic media (especially television), and print media (especially newspapers) in many areas in the country.